A Comparative Study of Congestion Management Strategies in Hybrid Electricity Markets (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—The rapid evolution of electricity markets toward hybrid models—integrating both regulated and deregulated structures—has intensified the need for effective congestion management strategies to ensure system reliability, market efficiency, and fair access to transmission networks. This paper presents a comprehensive comparative study of various congestion management techniques employed in hybrid electricity markets, including redispatching, transmission pricing, optimal power flow (OPF)-based methods, and market-based mechanisms such as nodal and zonal pricing. The study evaluates these approaches based on key performance indicators such as cost efficiency, computational complexity, transparency, and market fairness. A simulation-based analysis using standard test systems is conducted to highlight the operational impacts and economic implications of each method under varying load and generation conditions. The results demonstrate that hybrid congestion management models, which combine technical optimization with market-based incentives, offer a more adaptive and economically balanced solution compared to traditional approaches. The study concludes with insights into the practical challenges, policy implications, and future research directions for implementing robust congestion management frameworks in evolving hybrid electricity markets.